Facilitating Uptake of Post-abortion Contraception for Young People in Kenya - Mbehero, Faith; Momanyi, Ruth; Hesel, Kate (Frontiers in Global Women's Health, 2022)
Globally, maternal mortality is unacceptably high, and unsafe abortion is the most easily preventable cause of maternal death. Post-abortion contraception, recognized as a High Impact Practice in Family Planning, can reduce rates of unintended pregnancies and unsafe abortion and ultimately save lives. Implementation of this, however, is limited, especially for young people. This case study documents strategies, results, and lessons learned from Planned Parenthood Global’s project in South West Kenya, which improved access to and provision of comprehensive abortion care, including safe abortion, post-abortion care and post-abortion contraception, at 80 public and private health facilities. By prioritizing training and mentorship of mid-level providers on both medical and surgical abortion care, post-abortion contraception and youth friendly services, in addition to community engagement and referrals, this intervention removes common barriers to care for women and young people. Eighty-five percent of abortion care clients served by the project accepted same-day contraception, with the vast majority—including 90% of clients aged 24 and under—choosing long-acting reversible contraception. The Closing the Gap project was funded by an anonymous donor.